Artificial intelligence and Islamic finance: A Scopus-based literature mapping through a PRISMA protocol - Azwar, Azwar; Usman, Abur Hamdi; Abdullah, Mohd Farid Ravi (Journal of Islamic Law on Digital Economy and Business, 2025)
Purpose – This study examines the development of copus-based literature on the application of Artificial Intelligence (AI) in Islamic finance with a specific focus on its legal-normative implications within the framework of Islamic law (Sharia). It seeks to identify prevailing trends, technological implementations, and multidisciplinary approaches shaping this emerging field while assessing how these developments interact with and potentially influence Sharia compliance standards, fatwas, and governance mechanisms in Islamic finance. Methodology – A Systematic Literature Review (SLR) based on the PRISMA protocol was applied. Data were retrieved exclusively from Scopus, using strict inclusion criteria to ensure relevance and quality. Findings – Academic interest in AI integration into Islamic finance has grown markedly since 2020, with conference proceedings dominating the output. AI technologies such as blockchain, cloud computing, and Natural Language Processing (NLP) have been explored in diverse contexts. Research reflects a multidisciplinary lens covering the technical, ethical, legal, and Sharia compliance dimensions. AI is viewed as a strategic enabler for financial inclusion, social fund management automation, and enhancement of maqāṣid al-sharīʿah–oriented services. Implications – The findings underscore the importance of scholars, regulators, and Sharia governance bodies in ensuring that AI adoption upholds fiqh muʿāmalāt and ethical imperatives. This mapping provides a foundation for future research and policymaking toward innovative Sharia-compliant AI systems. Originality – This research is among the first systematic reviews that explicitly map copus-based academic discourse on AI applications in Islamic finance using a PRISMA-based SLR approach. This emphasizes the interdisciplinary nature and growing international engagement in developing Sharia-compliant AI solutions.